A deep learning model based on dynamic contrast-enhanced magnetic resonance imaging enables accurate prediction of benign and malignant breast lessons - Chen, Yanhong; Wang, Lijun; Luo, Ran; Wang, Shuang; Wang, Heng; Gao, Fei; Wang, Dengbin (Frontiers in Oncology, 2022)
Objectives: To investigate the value of convolutional neural network (CNN) based on dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) in predicting malignancy of breast lesions. Methods: We developed a CNN model based on DCE-MRI to characterize breast lesions. Between November 2018 and October 2019, 6165 slices of 364 lesions (234 malignant, 130 benign) in 364 patients were pooled in the training/validation set. Lesions were semi-automatically segmented by two breast radiologists using ITK-SNAP software. The Standard of reference was histologic consequences. Algorithm performance was evaluated on an independent testing set of 1560 slices of 127 lesions in 127 patients using weighted sums of the area under the curve (AUC) scores. Results: The area under the receiver operating characteristic (ROC) curve was 0.955 for breast cancer prediction while the accuracy, sensitivity, and specificity were 90.3%, 96.2% and79.0%, respectively in the slice-based method. In the case-based method, the efficiency of the model changed by adjusting the standard for the number of positive slices. When a lesion with three or more positive slices was determined as malignant, the sensitivity was above 90% with a specificity nearly 60% and an accuracy higher than 80%. Conclusion: The CNN model based on DCE-MRI demonstrated a high accuracy for predicting the malignancy among the breast lesions. This method should be validated on a larger and independent cohort.